P145 Membranous and proliferative lupus nephritis – analysis of a nationwide multicentre cohort. (23rd March 2020) - Farinha, Filipa; Barreira, Sofia; Couto, Maura; Cunha, Margarida; Fonseca, Diogo; Freitas, Raquel; Inês, Luís; Luís, Mariana; Macieira, Carla; Rodrigues, Joana; Santos, Bernardo; Torres, Rita; et al.
Abstract : Background: Lupus Nephritis (LN) is one of the most severe manifestations of Systemic Lupus Erythematosus (SLE). We aimed to compare proliferative (PLN), membranous (MLN) and mixed LN regarding clinical and laboratory presentation, and serologic profiles. Previous work suggested that these groups differ in autoantibody profile and complement levels, but those reports mainly originate from single-centres. Methods: Multicentre observational study, with retrospective analysis of a prospective cohort, using data from the Portuguese registry of rheumatic diseases–Reuma.pt. Patients with biopsy-proven PLN, MLN and mixed LN were included. The first renal biopsy showing one of these classes was considered, for each patient. Groups were compared using Pearson's Chi-Square for categorical variables and One-Way ANOVA or Kruskal-Wallis for numerical variables. Results: 232 patients were included (87% females; 88.5% White Europeans). Median follow-up was 7 years (IQR 10.75; maximum 35 years). As seen in table1, the level of proteinuria did not differ between groups; however, MLN patients presented with significantly lower creatinine. Levels of complement were reduced in PLN and mixed LN but were normal in MLN patients, and this difference was statistically significant. Groups also differed regarding the proportion of positivity for anti-dsDNA (higher in PLN) and anti-RNP antibodies (higher in MLN). There was a lower SLEDAI in MLN, probably linked with the lower prevalence of anti-dsDNA antibodies and complement consumption in this group. Conclusions: Our results support previous findings from single-centre studies suggesting that MLN has a different serological profile than PLN, possibly reflecting different pathogenesis.